2021
DOI: 10.1093/noajnl/vdab038
|View full text |Cite
|
Sign up to set email alerts
|

H3K27M andTERTpromoter mutations are poor prognostic factors in surgical cases of adult thalamic high-grade glioma

Abstract: Background Thalamic high-grade gliomas (HGGs) are rare tumors with a dismal prognosis. H3K27M and telomerase reverse transcriptase promoter (TERTp) mutations reportedly contribute to poor prognoses in HGG cases. We investigated the outcomes of surgically treated adult thalamic HGGs to evaluate the prognostic significance of H3K27M and TERTp mutations. Methods We retrospectively analyzed 25 adult patients with thalamic HGG who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In the series of Park et al, [17] where 70% of the patient group consisted of patients with KPS 80 and above, the median overall survival was 21.8 months. In accordance with Park's findings, Osada et al [4] published the results of 12 H3K27M-mutant glioma patients, where 58.3% of the patients with KPS 80 and above, with a median OS of 22.8 months. Our analysis has demonstrated that patients with a KPS score of 50 are associated with a worse prognosis compared to higher KPS scores.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the series of Park et al, [17] where 70% of the patient group consisted of patients with KPS 80 and above, the median overall survival was 21.8 months. In accordance with Park's findings, Osada et al [4] published the results of 12 H3K27M-mutant glioma patients, where 58.3% of the patients with KPS 80 and above, with a median OS of 22.8 months. Our analysis has demonstrated that patients with a KPS score of 50 are associated with a worse prognosis compared to higher KPS scores.…”
Section: Discussionsupporting
confidence: 67%
“…Radiotherapy, with or without chemotherapy, is frequently the only effective option for patients with unresected or partially resected tumors, [3] with reported median survival times ranging between 8.76 and 22.8 months in the literature. [4,5] We retrospectively evaluated the results of radiotherapy with or without temozolomide for adult patients with H3K27M-altered midline gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of DMG patients with H3K27M alterations is poor, with a median survival period reported in the literature between 8.76 and 22.8 months [8][9][10]. The 2-year survival rate is less than 10% for patients receiving standard treatment, including surgery and adjuvant chemoradiation [11].…”
Section: Introductionmentioning
confidence: 99%
“…This was a retrospective study reviewing the medical records of patients with supratentorial adult diffuse gliomas and thalamic DMG who underwent debulking surgeries at our department between January 2009 and December 2022 [ 12 , 13 , 16 , 26 , 29 , 31 ]. The follow-up data until June 2023 were analyzed.…”
Section: Methodsmentioning
confidence: 99%